Investigation of the subtypes of developmental dyslexia in brazilian’s children - Germano, Giseli Donadon [UNESP]; Dos Santos Liporaci, Gabriela Franco [UNESP]; Capellini, Simone Aparecida [UNESP] (My University, 2016)
Dyslexia refers to individual differences in processing, often characterized by difficulties in early literacy, affecting the acquisition of reading, writing and spelling. They can also occur in cognitive failure, phonological and / or visual processes. Dyslexia can be classified into three subtypes: Phonological Dyslexia, Visual Dyslexia and Mixed dyslexia. The aim of this chapter was to investigate whether Brazilian’s students with developmental dyslexia could be classified according with subtypes. Sixty-six children with developmental dyslexia and normal Brazilian Portuguese children participated in this study. Were administered three tasks of phonological skills (phoneme identification, phoneme, and syllable blending) and three visual tasks (a letter global report task and two non-verbal tasks of visual closure and visual constancy). The results indicated that students with dyslexia presented lower performance when compared to students from the control group and to reading processes (identifying letters, same-different, lexical decision, understanding phrases, reading comprehension, reading words and reading nonwords), the phonological tests (phonemic identification phonemic combination, syllabic combination) and visual (constancy, visual closure and global print report). Two subgroups of children with developmental dyslexia were identified a single cognitive impairment, phonological or visual having another group presented a double deficit and some children showed no disorder. In this study, the results indicated the predominance of visual and mixed subtypes. Also, this study brings a contribution to heterogeneity of the dyslexic subtypes in Brazilian Portuguese.
Keywords: Developmental dyslexia; Phonological processing; Subtypes; Visual attention span; Visual processing